The Effect of Tax, Exchange Rate, and Leverage on Transfer Pricing Policy with Foreign Ownership as Moderating Variables (International Journal of Scientific Research and Management (IJSRM), 2022)
Abstract; In general, multinational companies that have affiliated relationships make transfer pricing policies. There are various motivations related to the transfer pricing policy This research aims to analyze the causal correlation of tax, exchange rate, and leverage on transfer pricing with foreign ownership as moderator. The research population is companies from manufacturing sector that listed on the IDX year 2017 until 2019. The sample of this research is 52 companies from manufacturing sector that were chosen based on purposive sampling, with the criteria of companies that have foreign ownership. The method of this research is a quantitative method, with panel data regression analysis. The results of this research are exchange rate and leverage have positive effect on transfer pricing, while tax has no effect on transfer pricing. Foreign ownership as a moderator wasn’t able to moderate the effect of tax, exchange rate, and leverage on transfer pricing. The implication of the research is that the dominant motives that trigger companies to do transfer pricing are exchange rates and leverage, not tax incentives. If the exchange rate increases, the company will sell to countries whose currency exchange rates strengthen so that the price of products/services will be cheaper and able to compete. Keywords: Tax, Exchange Rate, Leverage, Transfer Pricing, Foreign Ownership